Percepção dos enfermeiros sobre fatores relacionados à ocorrência de eventos adversos em um hospital pediátrico - Pimentel, Sidiany Mendes (Universidade Federal do Tocantins, 2020)
This research aimed to identify the importance attributed by nurses of a children's hospital to elements of the physical and organizational structure and the work process for the occurrence of adverse events, considering the ideal and real plans (present in their environment). practice). This is a descriptive, cross-sectional research with a quantitative approach, conducted with nurses from the Palmas Public Children's Hospital through the application of the Adverse Events Predisposition Scale with Likert scale response interval. Data collection took place from August to November 2019, following approval of this study by the Local Ethics Committee through opinion CAAE 08269319.0.0000.5519. Data analysis was performed using descriptive statistics. The final sample consisted of 22 nurses, of which 50% had high perception for the structure domain and 68.18% had high perception for the process domain, regarding factors that may predispose to the occurrence of adverse events. The average response to the structure domain was 4.9 at the ideal level and 2.95 at the real level. In the process domain, the average was 4.8 for the ideal and 2.7 for the real one. ideal and the real for investigated items. The study reinforces the need to adopt evidence-based practices and strategies recommended by the Ministry of Health to reduce adverse events such as those expressed in the Anvisa Protocols and in the National Patient Safety Program Manual.